2020
DOI: 10.3390/v12080786
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequencing of a Camelpox Vaccine Reveals Close Similarity to Modified Vaccinia virus Ankara (MVA)

Abstract: Camelpox is a viral contagious disease of Old-World camelids sustained by Camelpox virus (CMLV). The disease is characterized by mild, local skin or severe systemic infections and may have a major economic impact due to significant losses in terms of morbidity and mortality, weight loss, and low milk yield. Prevention of camelpox is performed by vaccination. In this study, we investigated the composition of a CMLV-based, live-attenuated commercial vaccine using next-generation sequencing (NGS) technology. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
2
3
0
1
Order By: Relevance
“…Except for two con rmed genomic deletions, the whole genome sequence of this vaccine was shown to closely resemble that of VACV-MVA, supporting our earlier study in which we reported that two gene regions of this vaccine resembled the aforementioned strain [33]. Our ndings also corroborate with a previous study that used short read Illumina sequencing, and a reference guided assembly to generate a partial Ducapox genome, wherein the authors noted the putative deletions, but could con rm the validity of the deletions due to the both the assembly pipeline and sequencing technology used [34]. At 159,696 bp in length, the vaccine genome, to our knowledge, is the smallest amongst the non-vector derived orthopoxviruses.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Except for two con rmed genomic deletions, the whole genome sequence of this vaccine was shown to closely resemble that of VACV-MVA, supporting our earlier study in which we reported that two gene regions of this vaccine resembled the aforementioned strain [33]. Our ndings also corroborate with a previous study that used short read Illumina sequencing, and a reference guided assembly to generate a partial Ducapox genome, wherein the authors noted the putative deletions, but could con rm the validity of the deletions due to the both the assembly pipeline and sequencing technology used [34]. At 159,696 bp in length, the vaccine genome, to our knowledge, is the smallest amongst the non-vector derived orthopoxviruses.…”
Section: Discussionsupporting
confidence: 91%
“…The vaccine has since been found to contain two gene regions that more closely resembled that of VACV strain Modi ed Vaccinia Ankara (VACV-MVA) [33]. A separate study of the strain using second generation WGS found the vaccine genome matches that of VACV-MVA, with the exception of two genomic deletions (5195 and 890 bp in size), however, the authors questioned the authenticity of these genomic deletions due to both the reference-based assembly approach adopted, and the low sequencing coverage of the genome [34]. We present a sequencing and annotation pipeline for long read de novo assembly of Poxvirus genomes and identify putative epigenetic modi cations within the genome.…”
Section: Introductionmentioning
confidence: 99%
“…Except for two confirmed genomic deletions, the whole genome sequence of this vaccine was shown to closely resemble that of VACV-MVA, supporting our earlier study in which we reported that two gene regions of this vaccine most closely resembled those of the aforementioned strain 34 . Our findings also corroborate with a previous study that used short read Illumina sequencing, and a reference guided assembly to generate a partial Ducapox genome, wherein the authors noted the putative deletions, but could not confirm the validity of the deletions due to the both the assembly pipeline and sequencing technology used 35 . At 159,695 bp in length, the vaccine genome, to our knowledge, is the smallest amongst the non-vector derived orthopoxviruses.…”
Section: Discussionsupporting
confidence: 78%
“…The vaccine has since been found to contain two gene regions that more closely resembled that of VACV strain Modified Vaccinia Ankara (VACV-MVA) 34 . A separate study of the strain using second generation WGS found the vaccine genome matches that of VACV-MVA, with the exception of two genomic deletions (5195 and 890 bp in size), however, the authors questioned the authenticity of these genomic deletions due to both the reference-based assembly approach adopted, and the low sequencing coverage of the genome 35 . We present a sequencing and annotation pipeline for long read de novo assembly of Poxvirus genomes and identify putative epigenetic modifications within the genome.…”
Section: Introductionmentioning
confidence: 99%
“…Camel pox has been reported in all other countries where camel farming takes place. Symptoms of camel pox include the development of fever accompanied by lesions in the form of rash both on the skin and mucous membranes in the respiratory organs and oral cavity of animals ( Marcacci et al , 2020 ). Depending on the severity of the disease, clinical signs of the CMLV include manifestations of different levels of systemic infection, ranging from mild to severe ( Saud et al , 2021 ).…”
Section: Introductionmentioning
confidence: 99%